2020
DOI: 10.1007/s11469-020-00222-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Italian Version of the Smartphone Application-Based Addiction Scale (SABAS)

Abstract: The aim of the present study was to test the psychometric properties of the Italian version of the Smartphone Application-Based Addiction Scale (SABAS; Csibi et al., International Journal of Mental Health and Addiction, 16, 393-403, 2018), a short and easy to use six-item tool for screening the risk of addiction to smartphone-based applications. A further goal was to explore the impact on smartphone addiction of several variables related to smartphone use habits, perceived quality of life, and sociability meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 69 publications
5
16
0
Order By: Relevance
“…This indicates that the SABAS is reliable in assessing the students’ challenges with smartphone use. These findings (unidimensional structure and reliability) are similar to previous studies ( 15 , 35 , 37 39 , 41 ). Also, the floor effect (25.7%) was higher than the suggested cut-off and that in previous studies ( 15 , 37 , 57 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the SABAS is reliable in assessing the students’ challenges with smartphone use. These findings (unidimensional structure and reliability) are similar to previous studies ( 15 , 35 , 37 39 , 41 ). Also, the floor effect (25.7%) was higher than the suggested cut-off and that in previous studies ( 15 , 37 , 57 ).…”
Section: Discussionsupporting
confidence: 92%
“…A CFA of SABAS demonstrated a unidimensional structure with satisfactory psychometric properties which include internal consistency (Cronbach’s α of 0.75), criterion and construct validity among Hong Kong university students ( 15 ). Furthermore, other studies reported acceptable psychometric properties in different languages which includes Persian ( 37 ), English ( 38 ), Turkish ( 39 , 40 ), Italian ( 41 ), Serbian ( 42 ), and Hungarian ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…The psychometric properties of the SABAS and the Chinese SABAS have been found to be satisfactory. [20][21][22][23][24] The present study also showed that the Chinese SABAS had good internal consistency (α = 0.88).…”
Section: Smartphone Application-based Addiction Scale (Sabas)supporting
confidence: 71%
“…Although different instruments for PMPU have been used [ 16 ] and adapted [ 61 , 62 , 63 ] in Italian populations of adolescents and adults, the present study on the adaptation of the TMD-brief to the Italian context has the advantage of primarily focusing attention on the adolescent population. De Pasquale et al [ 61 ] reported the Italian validation of a 10-item questionnaire among 633 adolescents and young adults showing a one-factor structure.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses showed a seven-factor structure for the questionnaire, namely: Loss of control of smartphone use, Nomophobia, Smartphone-mediated communication, Emotion regulation through smartphone usage, Smartphone support to romantic relationships, Smartphone tasks support and Awareness of smartphone negative impact. Soraci et al [ 63 ] tested the psychometric properties of a previous 6-item questionnaire among 205 Italian adults showing a unidimensional factor. By contrast, we specifically focused on the problematic use of smartphones among Italian adolescents.…”
Section: Discussionmentioning
confidence: 99%